Impact of a quality improvement intervention on neonatal mortality in a regional hospital in Burkina Faso. (17th December 2022) - Ouedraogo, Paul; Villani, Paolo Ernesto; Tubaldi, Lucia; Bua, Jenny; Uxa, Fabio; Dell'Anna, Carmen; Cavallin, Francesco; Thomson, Merran; Plicco, Cecilia; Chiesi, Maria Paola
Abstract: Background: The neonatal period is the most vulnerable time in terms of a child's survival, with mortality during this period accounting for approximately half of the deaths before the age of 5 years. The Neonatal Essential Survival Technology (NEST) project is a program aiming to reduce mortality by improving the quality of neonatal care in sub-Saharan Africa. This study presents the evaluation of the first phase of the NEST intervention program at Saint Camille Hospital Ouagadougou (HOSCO), Burkina Faso, in terms of the reduction in neonatal mortality. Methods: This is a retrospective analysis, based on "pre-intervention" data collected in 2015, and "post-intervention" data collected in 2018, including all infants admitted to the neonatal unit of HOSCO. The intervention period (2016 and 2017) comprised a structured quality improvement process conducted by a multidisciplinary working group that focused on improving infrastructure, equipment, training and use of clinical protocols, team working within the neonatal unit and with other hospital departments, and communication with referring healthcare facilities. Mortality data were compared pre- vs. post-intervention using a logistic regression model. Results: The analysis included 1427 infants in the pre-intervention period, and 819 post-intervention. In both time periods, more than 75% of admissions were infants with low birth weight, and nearly 50% were very low birth weight. Post-intervention, while there was a decrease in overall admission, the proportion of multiple births increased from 20% to 24% ( p = .01). The overall mortality rate was 44.9% (641/1427) pre-intervention, and 42.2% (346/819) post-intervention (OR 0.90, 95% confidence interval (CI) 0.76–1.07; p = .23). Adjusting for clinically relevant factors, the intervention was not associated with a change in overall mortality (OR 1.39, 95% CI 0.91–2.12; p = .13), but was associated with a reduced likelihood of mortality in outborn infants compared to inborn infants (OR 0.57, 95% CI 0.36–0.92; p = .02). Conclusions: The first phase of the NEST quality improvement program was associated with a decrease in mortality in outborn infants admitted to the neonatal unit at HOSCO. Long-term assessment is expected to provide a more comprehensive evaluation of the program in a low-income setting.